Hubungan Umur Dan Paritas Ibu Hamil Dengan Anemia Di Rumah Bersalin Hj. Dermawati Nasution Tembung - Mardha, Muthia Sari; Syafitri, Endriyani; Panjaitan, Ivan S (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Background; Pregnant women certainly want a healthy pregnancy, which should always check their pregnancy so that they get counseling about pregnancy danger signs such as anemia. Anemia in pregnant women is strongly associated with mortality and morbidity in mothers and babies. Reports from the profile of maternal MMR districts / cities reported in North Sumatra in 2014 were only 75 / 100,000 live births. Objectives; The purpose of this study was to determine the relationship between the age and parity of pregnant women with anemia at the HJ. Dermawati Nasution Maternity Hospital in 2018. Methode; The type of research used was Analytical Survey with Cross Sectional approach. The location of the study was HJ. Dermawati Nasution Maternity Hospital Tembung, the time of the study was from January to finish in 2018. The population in this study was 35 pregnant women who were sampled using accidental sampling techniques. Results; Based on the results of the study using the Chi-Square test, it was known that the relationship between age and parity of anemia was age with p = 0.016 (<0.05) which stated that there was a significant relationship between age and anemia, while parity with p = 0.013 (p <0), 05) stated that there was a significant relationship between parity and anemia. Conclusion; The conclusion in this study was that there was a relationship between the age and parity of pregnant women with anemia at the HJ. Dermawati Nasution Maternity Hospital 2018. It was recommended for pregnant women to visit the HJ. Dermawati Nasution Maternity Hospital Tembung to add information and knowledge of pregnant women to be more aware of their pregnancies and be able to care for and maintain pregnancy so that complications in pregnancy will not occur.